EKSISTENSI TEKNOLOGI PENDIDIKAN DALAM INOVASI PEMBELAJARAN - Suhirman Suhirman (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
Technology  education is a complex and  integrated process that  includes: human, environmental, systems, tools,  ideas,  procedures and  organization. Technology  education in the  journey,  is a solution  and anticipatory, by providing solutions  to overcome the problem of learning  and prepare students for a better  life in the future, because life in the days to come, full of competition and  challenges, necessitating their learning innovations, Therefore,  the existence of educational technology has a strategic  role in preparing learners who have a competitive edge  in competition, both from within and from abroad